Pengaruh Akuntanbilitas dan Transparansi Terhadap Kepuasan Muzakki pada Baznas Kota Jambi - Decka Aisyah; Elyanti Rosmanidar; Sri Rahma (AKUA: Jurnal Akuntansi dan Keuangan, 2022)
This study aims to determine the characteristics of muzakki who pay zakat in BAZNAS Jambi City and analyze the effect of each variable, namely accountability and transparency on muzakki satisfaction. The dependent variable in this study is satisfaction while the independent variables are accountability and transparency. The population in this study is muzakki who pay zakat at BAZNAS Jambi City. The sample method used is purposive sampling and obtained as many as 100 respondents. The data in this study were taken using a questionnaire distributed to muzakki who pay zakat at BAZNAS Jambi City. The analytical method used in this research is multiple linear regression. The results of the study found that the characteristics of muzakki who pay zakat in BAZNAS Jambi City are based on gender, age, education, occupation, income, length of time being a muzakki. Based on the results of the regression coefficients, it shows that accountability (X1) has a positive and significant effect on muzakki satisfaction with a value of 0.001 <0.05. Transparency (X2) has a positive and significant effect on muzakki satisfaction with a value of 0.001 >< 0.05. Accountability and transparency simultaneously affect the satisfaction of muzakki with a value of 0.001 < 0.05.